(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
In the article religion Islam rules analyzed which entered the territory of Central Asia during the Arab caliphate, promoted monotheism, unlike other religions, and put an end to the state of spiritual emptiness in the country by the helping historical sources.